Pendampingan Hukum LBH dalam Cerai Talak Ghoib: Analisis Yuridis Putusan 956/Pdt.G/2025/PA.Tnk. - Adam Faisal Malik; M. Lutfi (Universitas Medan Area, 2025)
Context and problems in this study The case of Talak Ghoib Divorce in the Religious Court often faces the complexity of evidence and the procedure for summoning advertisements, becoming a serious obstacle for the poor to access justice (access to justice). This study aims to analyze the strategic role of legal assistance by LBH Advocates in Decision Number 956 / Pdt.G / 2025 / PA.Tnk to guarantee the rights of the Petitioner Muhammad Mujib Bin M.Chomsin in accordance with the Legal Aid Law Number 16 of 2011. Using the juridical-normative case study method, this method is applied to analyze the legal norms and judicial prudential practices of the Panel of Judges. This study found two main things. First, the Panel of Judges applied high judicial prudence, demanding evidence from the Respondent Ghoib for seven years and absolute compliance with the procedure for summoning advertisements (Article 140 RBg) to legitimize the default decision. Second, the role of LBH advocates is instrumental in facilitating administrative requirements (SKTM) and formulating a careful evidentiary strategy, transforming potential procedural failures into effective legal certainty for poor clients. LBH assistance is a functional realization of the principles of access to justice and equality before the law in Religious Courts. The contribution of this research is to present an empirical model of how structural legal aid mitigates procedural inequalities for the poor.